The Enhancing User Experience for Mother and Children Services at Sungai Duren Health Center in Muara Enim, Indonesia - Rasmila Rasmila; Muhammad Fharid Akbar (PIKSEL : Penelitian Ilmu Komputer Sistem Embedded and Logic, 2024)
In the present digital age, it is imperative for us to harness the advancements in technology, particularly in the healthcare sector. The initial step in a medical consultation involves health screening. Traditional health screening relies on interviews and paper documentation. However, over time, the use of paper can lead to data accumulation and potential loss. This research focuses on the creation of a user-friendly mobile application for Mother and Child Health Services, utilizing the Design Sprint method. The Sungai Duren Health Center in Muara Enim Regency, Indonesia, currently lacks essential technology for disseminating information about Mother and Children Health Services. Implementing supporting technology is crucial for enhancing service quality for health center participants. The anticipated benefits extend to academia, writers, and the users of the application.